Genetic and heritability estimates of landrace upland rice accessions grown in rainforest agro-ecological zone of Nigeria - Agbowuro, Gbenga Oluwayomi; Salami, Ayodeji Ekundayo; Aluko, Matthew; Olajide, Olubunmi Olufunke; Afolabi, Micheal Segun (Journal of Pure and Applied Agriculture, 2023)
The basic understanding and knowledge of genetic variability within a plant population are highly fundamental for its improvement by the plant breeders. Research work was conducted to estimate the extent of genetic variability, heritability, and genetic advance as percent of mean of landrace upland rice accessions that are predominantly grown in the rainforest agro-ecological zone of Nigeria. Ten landrace upland rice accessions constituted the treatment and were laid in randomized complete block design with three replications in three locations between March to November 2019. Analysis of variance revealed significant differences (P<0.01) among the accessions and the environments except for the number of tillers per plant while accession by environment interaction differs significantly for all the traits though at different levels except the numbers of tillers per plant. Accession 1 recorded the highest grain yield (1.72) followed by accession 2 (1.38), accession 8 (1.36), accession 3 (1.29), and accession 4 (1.04) accordingly while accession 7 (0.75) had the least grain yield across the locations. Heritability (broad-sense) estimates ranged from (61.4393%) grain yield to (99.6028%) plant height. Moderate to high phenotypic and genotypic coefficients of variation and genetic advances as a percent of mean were recorded for all the traits. Moderate to high estimates of genotypic and phenotypic coefficients of variation, and genetic advances as a percent of mean coupled with high heritability (broad-sense) for these traits is an indication that the traits are governed by additive genetic action. Hence, improvement of these traits can be made through selection. © 2021 Department of Agricultural Sciences, AIOU